The Influence of Green Human Resource Management and Work-Life Balance on Environmental Performance Mediated by Green Innovation - Heni Purwanti; Mafizatun Nurhayati (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2026)
Purpose – This study aims to examine the influence of Green Human Resource Management (GHRM) and Work-Life Balance (WLB) on Environmental Performance (EP), with Green Innovation (GI) as a mediating variable, within the context of a manufacturing company in Indonesia. Methodology/approach – A quantitative approach using Partial Least Square Structural Equation Modeling (PLS-SEM) was employed to analyze data collected through structured questionnaires distributed to 100 permanent employees of PT. Sankei Gohsyu Industries. The constructs were measured using validated indicators derived from prior studies. Findings – The results reveal that GHRM has a significant positive effect on both EP and GI. WLB significantly influences EP but does not significantly affect GI. Additionally, GI does not significantly impact EP and fails to mediate the relationship between GHRM and EP, nor between WLB and EP. These findings suggest that while green HR practices and work-life balance are vital in enhancing environmental outcomes, green innovation alone may not yet serve as an effective mediating mechanism in this organizational setting. Novelty/value – This research contributes to the growing body of literature on sustainable HRM by clarifying the distinct roles of green HR practices and work-life balance in fostering environmental performance. It also highlights the limited mediating role of green innovation in this relationship, providing practical implications for HR and environmental policy strategies in the manufacturing sector of emerging economies.